Generation Expansion Planning Problem Considering Uncertainty - Adelino J. C. Pereira (2007)
The fundamental aim of an electric power utility consists in satisfying the demand and energy requirements of its customers at the lowest possible operating cost and with an acceptable level of continuity and quality of electricity supply. This objective involves the two basic aspects of economy and adequacy. In this context, generation expansion planning is one of the most important planning activities in the electric utilities and it is crucial to attain the referred objective. In this paper we describe a generation expansion-planning algorithm that considers various types of units and capacities, operating constraints and different demand scenarios. The solution approach is based in a two-stage stochastic linear program formulation in which we used a Decomposition approach. The proposed paper includes a Case Study to illustrate and discuss the effectiveness of the proposed resource planning approach.